Effects of physical exercise on the elderly: a systematic review - Paks, Karolina; Pelczar, Monika; Gajda, Zuzanna; Schendzielorz, Jessika; Prosowski, Jakub; Starosta, Barbara; Brzychcy, Bartosz; Brzychcy, Karolina; Hetnar, Paulina; Jench, Ewa (Quality in Sport, 2025)
Background: The population of Europe is aging, and the majority of individuals over 65 do not engage in sports activities, spending most of their day in a sedentary position. Consequently, the prevalence of age-related diseases, such as sarcopenia, dementia, osteoporosis, osteoarthritis, falls, frailty syndrome, and depression, is expected to rise. Aim: This article emphasizes the importance of physical exercise among older adults by presenting evidence on how incorporating or increasing physical activity can help counteract age-related health conditions. Given that this intervention is cost-free and has the potential to significantly improve seniors’ quality of life, it represents a highly relevant public health measure. Material and methods: A systematic review of selected literature was conducted using the PubMed, Google Scholar, and Web of Science databases, using keywords such as: “Exercise in elderly”, ‘Sarcopenia’ and “Physical activity seniors”. The analysis focused on peer-reviewed articles published between 2008 and 2025. Results and Conclusions: Physical activity provides numerous health benefits for older adults, with moderate- to high-intensity exercise demonstrating particularly significant effects. Resistance exercise is effective against sarcopenia, frailty syndrome, falls, osteoporosis, lumbar pain, depression and anxiety disorders. Aerobic exercise affects lumbar pain, depression and anxiety disorders, and possibly cognitive impairment. Most studies observed these beneficial effects following a 12-week intervention period, at least three times weekly, with individual sessions lasting no less than 60 minutes. Regular exercise is crucial for promoting healthy aging, offering comprehensive benefits that include reduced all-cause mortality, lower risk of chronic diseases, and decreased likelihood of premature death.